Refugees or migrants : pre-modern Jewish population movement - Chazan, Robert (Yale University Press, 2018)
For millennia, Jews and non-Jews alike have viewed forced population movement as a core aspect of the Jewish experience. This involuntary Jewish wandering has been explained as the result of divine punishment, or as a response to maltreatment of Jews by majority populations, or as the result of Jews' acceptance of their minority status perpetuating the maltreatment and forced migration. In this absorbing book, Robert Chazan explores these various accounts, and argues that Jewish population movement was in most cases voluntary, the result of a Jewish sense that there were alternatives available for making a better life.